Bridging Gaps, Breaking Barriers, and Building Capacities in Online Marketplaces - Connie Bayudan-Dacuycuy; Leih Maruss V. Sinsay (Philippine Institute for Development Studies (PIDS), 2022)
As the Fourth Industrial Revolution transforms the conduct of work and enterprises, inequalities and the digital-spatial divide become front and center of conversations that aim to promote online marketplaces and maximize their benefits. This paper takes stock of the development in human capital, labor market, and e-commerce, identifies state-led initiatives to build capacities, and analyzes barriers and gaps in labor and retail platforms. Data collected through desk reviews and key informant interviews with stakeholders were synthesized to highlight state-led initiatives and programs related to platform work, identify barriers to participation in the digital economy, and draw recommendations to address gaps. The paper finds that several state-led programs and initiatives for online marketplaces and legislative agenda related to the digital economy are in place. Despite this, the paper finds that 1) barriers related to gender roles, business environments, and financing exist and 2) gaps in social protection, digital competencies, and infrastructure support remain. Some directions to bridge gaps, break barriers to participation, and build capacities are forwarded to harness the full potential of labor and retail platforms.
Keywords: 330; Online marketplaces; platform work; freelancing; human capital; labor; and retail platforms